Fungsi Hukum Administrasi Negara dalam mewujudkan Pemerintah yang Bijak - Andhyca Moza Mahesa Antony (JURNAL HAK : Kajian Ilmu Hukum, Administrasi Negara, dan Komunikasi, 2025)
State Administrative Law has an important function in regulating, directing, and controlling the administration of government so that it runs in accordance with legislation and the principles of the rule of law. Through the principles of legality, accountability, transparency, and the general principles of good governance (AUPB), State Administrative Law serves as a guideline for administrative officials in exercising their authority and preventing abuse of power. In addition, Administrative Law also serves to provide legal protection to the public against harmful government actions or decisions. With the existence of oversight mechanisms and legal remedies, a balance is created between government authority and the rights of citizens. Therefore, Administrative Law plays a vital role in realizing wise governance, namely governance that is fair, responsible, and oriented towards the public interest and welfare.